Transcriptome Profiling of Developing Ovine Fat Tail Tissue Reveals an Important Role for MTFP1 in Regulation of Adipogenesis - Han, Jiangang; Ma, Sijia; Liang, Benmeng; Bai, Tianyou; Zhao, Yuhetian; Ma, Yuehui; MacHugh, David E.; Ma, Lina; Jiang, Lin (Frontiers in Cell and Developmental Biology, 2022)
Fat-tail sheep exhibit a unique trait whereby substantial adipose tissue accumulates in the tail, a phenotype that is advantageous in many agroecological environments. In this study, we conducted histological assays, transcriptome analysis and functional assays to examine morphogenesis, characterize gene expression, and elucidate mechanisms that regulate fat tail development. We obtained the microstructure of tail before and after fat deposition, and demonstrated that measurable fat deposition occurred by the 80-day embryo (E80) stage, earlier than other tissues. Transcriptome profiling revealed 1058 differentially expressed genes (DEGs) with six markedly different expression trends. GSEA enrichment and other downstream analyses showed important roles for genes and pathways involving in metabolism and that mitochondrial components were specifically overexpressed in the fat tail tissue of the 70-day embryo (E70). One hundred and eighty-three genes were further identified by leading edge gene analysis, among which, 17 genes have been reported in previous studies, including EEF1D, MTFP1, PPP1CA, PDGFD. Notably, the MTFP1 gene was highly correlated with the expression of other genes and with the highest enrichment score and gene expression change. Knockdown of MTFP1 in isolated adipose derived stem cells (ADSCs) inhibited cell proliferation and migration ability, besides, promoted the process of adipogenesis in vitro.